Creating economic growth : lessons for Europe - Magnani, Marco; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
As national leaders struggle to revive their economies, the people of Europe face a stark reality, which has created an opportunity for local leaders and citizen movers and shakers to rise to the occasion to spur revitalization from the bottom up. The author offers a six-point plan to prosperity.
Keywords: Economic development -- Europe; Economic policy